2013
DOI: 10.1074/jbc.m112.421156
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Transcription of Human Matrix Metalloproteinase 13 (MMP13) and Interleukin-1β (IL1B) Genes in Chondrocytes Depends on Methylation of Specific Proximal Promoter CpG Sites

Abstract: Background:The role of DNA methylation in musculoskeletal diseases is poorly understood. Results: Methylation of specific CpG sites in the MMP13 and IL1B promoters correlates strongly with gene activity in human cartilage. Conclusion: Specific CpG site methylation inhibits MMP13 transactivation by HIF-2␣. Significance: Our findings offer new insight on the impact of epigenetic control of a joint disease that can affect adults throughout life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 67 publications
6
137
5
Order By: Relevance
“…The increasing evidences revealed that the CpG methylation of promoter suppress the gene expression by inhibiting the transcription factors to bind their binding sites that contain CpG (Fujii et al, 2006;Hou et al, 2012;Hashimoto et al, 2013). For example, it has been reported that 5-Aza-CdR treatment increased the transcription factors of SP-1 binding to its binding sites in the sEH gene promoter (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The increasing evidences revealed that the CpG methylation of promoter suppress the gene expression by inhibiting the transcription factors to bind their binding sites that contain CpG (Fujii et al, 2006;Hou et al, 2012;Hashimoto et al, 2013). For example, it has been reported that 5-Aza-CdR treatment increased the transcription factors of SP-1 binding to its binding sites in the sEH gene promoter (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Alterations in DNA methylation patterns have been observed in OA chondrocytes, particularly a loss of DNA methylation at the promoters and the concurrent "unsilencing" of various OA-associated genes including MMP3, 9, and 13, ADAMTS4, IL-1β, and iNOS (14,33,34). Recently, Professor Bhutani's team reported a remarkable dysregulation of 5hmC homeostasis in patients with OA, with increases in global 5hmC levels observed in OA chondrocytes when compared to normal chondrocytes (35).…”
Section: Epigenetics and Oamentioning
confidence: 99%
“…These studies started with an investigation of the epigenetic regulation of the expression of genes coding for proteins that have a known central role in the homeostasis of joint tissue, and in particular cartilage (14). There have also been direct investigations of the differences in expression levels of regulatory RNAs between OA and non-OA cells, the aim being to identify key RNAs that could initiate or exacerbate disease development (15,16).…”
Section: Epigenetics and Oamentioning
confidence: 99%
“…Thoms et al found that hypoxia suppressed the destruction and induced production of human cartilage through the regulation of hypoxia-inducible factor1a (HIF-1a) and HIF-2a and their interaction with SOX9 [34]. HIF-2a has been reported to mediate the transcriptional activity of the catabolic gene MMP13 under different methylation statuses in chondrocytes [35]. HIFs can also alternatively interact with histone deacetylase (HDAC) inhibitors and modulate their activities, resulting in the determination of stem cell fate [36].…”
Section: Hypoxiamentioning
confidence: 99%